Undang-Undang Nomor 21 Tahun 2007 tentang Pemberantasan Tindak Pidana Perdagangan Orang dalam Perspektif Hukum Islam - Nuraeni, Neni; Kania, Dede (al-'adalah, 2017)
Human Traffickingis one of the most common crimes occurs in Indonesia. To eradicate this crime, the government issued the 21/2007 of Human Trafficking Act (UU PTPPO). The statue sanctions persons committing the crime and providing protection to witnesses and victims. The law accomodate a number of penalties for the perpetrators of this crime, ranging from principal punishment, in the form of imprisonment and fine, to additional criminal and ballast. Although Islamic law does not explicitly regulate this crime, it is clearly contrary to Islamic principles of freedom, independence, equality and human dignity.